2018
DOI: 10.1016/j.jconrel.2018.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun amorphous solid dispersions of poorly water-soluble drugs: A review

Abstract: The development of oral dosage forms for poorly water-soluble active pharmaceutical ingredients (APIs) is a persistent challenge. A range of methods has been explored to address this issue, and amorphous solid dispersions (ASDs) have received increasing attention. ASDs are typically prepared by starting with a liquid precursor (a solution or melt) and applying energy for solidification. Many techniques can be used, with the emergence of electrospinning as a potent option in recent years. This method uses elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
164
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(173 citation statements)
references
References 294 publications
(385 reference statements)
3
164
0
6
Order By: Relevance
“…Although EHDA processes (including e‐jet printing, electrospraying, and electrospinning) are fast developing to the multiple‐fluids ones, such as coaxial (Hai et al., ; Yu et al., ), triaxial (Liu et al., ; Yang et al., ), their microformation mechanisms are still unclear (Yang, Zhang, Liu, Wang, & Yu, ; Yu, Li, Williams, & Zhao, ). Thus, on one hand, the single‐fluid electrospraying and electrospinning are still the mainstreams of these fabrication methods.…”
Section: Introductionmentioning
confidence: 99%
“…Although EHDA processes (including e‐jet printing, electrospraying, and electrospinning) are fast developing to the multiple‐fluids ones, such as coaxial (Hai et al., ; Yu et al., ), triaxial (Liu et al., ; Yang et al., ), their microformation mechanisms are still unclear (Yang, Zhang, Liu, Wang, & Yu, ; Yu, Li, Williams, & Zhao, ). Thus, on one hand, the single‐fluid electrospraying and electrospinning are still the mainstreams of these fabrication methods.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previous publications before this time point, they concluded that the shell working fluids must be electrospinnable for successfully carrying out a coaxial process and for creating a core-shell nanostructure [24]. However, Yu, et al broke this concept to develop a modified coaxial electrospinning, in which the sheath working fluid could be a pure solvent [12]. The modified process was successfully conducted to generate fibers from a concentrated polymer solution, which was impossible for a single-fluid process owing to the frequent clogging of the spinneret's nozzle.…”
Section: The Modified Coaxial Electrospinning With An Unspinnable Shementioning
confidence: 99%
“…These advanced techniques should greatly expand the capability of electrospinning in generating a wide variety of complex nanostructures. However, among all the complex nanostructures, the core-shell should be the most fundamental and the most important one [12]. It is not only because that many other complicated nanostructures can be viewed as a derivative of core-shell structure, but also this fundamental nanostructure has been broadly demonstrated to be extremely useful in designing and developing a wide variety of functional nanomaterials for applications in almost all the scientific fields [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to general pharmaceutics, the development of solid dispersions relies on having access to suitable pharmaceutical technologies and carriers to prepare the formulation (Yu et al, 2018). Previously, we demonstrated that the solvent evaporation method using anhydrous ethanol as a solvent enabled the successful development of TBESD-ASD.…”
Section: Preparation Of Tbesd-asdmentioning
confidence: 99%